Design of a non-human proctoring and authentication system for mobile phone-based online examination - Ubochi, Brendan; Oluleye, Emmanuel; Odeyemi, Charity; Ubochi, Chinyere (Journal of Computer Sciences Institute, 2025)
Proctored computer-based examinations present challenges that are associated with high operational costs, logistical difficulties, and scalability limitations. While mobile phone applications have emerged as a solution for overcoming the challenges posed with maintaining extensive computer laboratories for assessments, persistent security concerns and fraud in non-proctored examinations remain. In this work, a specialized fraud-resistant mobile phone application is developed for conducting tests and examinations. It leverages on the Flutter framework in order to ensure compatibility with both iOS and Android devices. By disabling screenshots, activating a lockdown mode and using a random user authentication prompt, the developed software can be used to combat cheating and impersonation during an examination. The results indicate that the mobile application can effectively detect and prevent cheating attempts, employing a lockdown mode that automatically submits examination upon detection of irregularities.